Evaluation of revised national tuberculosis control programme in rural Puducherry - Rangasamy, Surendar; Marimuthu, Arthi; Subramanian, Rajkumar; A., Narayan K. (International Journal Of Community Medicine And Public Health, 2019)
Background: WHO estimates that annually 3 million deaths occurs due to tuberculosis and will reach to more than one billion in 2020. In India, more than 40% of population is infected. The revised national tuberculosis control programme (RNTCP) uses directly observed treatment, short-course (DOTS) therapy strategy to reduce mortality and morbidity, reduce transmission. Compliance to DOTS therapy is one of the important factors that affect the treatment outcome. Hence this study was done to assess the drug compliance rate of adults registered under RNTCP in the past one year and first three months after starting the study and to explore the factors associated with drug compliance. Methods: A longitudinal study was done in Bahour Commune Panchayat with subjects registered under RNTCP from January 2011 to March 2012. They were followed-up by house visit, interviewed using a semi-structured questionnaire. Results: The mean age was 44±13 years, 35 (68.6%) males were illiterate. About 60 (85.7%) belong to Class IV socio-economic status; 15 (29.4%) and 33 (64.7%) of adults had smoking and alcohol intake respectively; 03 (04.3) were diabetic. The treatment compliance rates were cured 64.3% (45/70), completed 27.1% (19/70), default 2.9% (02/70), failure 5.7% (04/70). Conclusions: Male being diseased in the productive age-group, will not only affect the health of the patient but also affect the family’s economic status. Most of the males gave history of alcohol intake, for which they require constant motivation for compliance to the treatment.